HUMAN EMOTIONAL LEVELS: HAWKINS SCALE THEORY AND ITS CORRELATION WITH THE CONCEPT OF NAFS IN THE QUR'AN - Ira Bariroh; Ainul Yakin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to analyze the relationship between David R. Hawkins emotional consciousness level theory and the concept of nafs in the Quran. In transpersonal psychology, Hawkins maps human consciousness through the map of consciousness, placing emotions along an energy spectrum from the lowest (shame, guilt, fear) to the highest (love, peace, enlightment). Meanwhile, the Quran discusses human spiritual dynamics through the concept of nafs, which comprises levels such as nafs al-ammarah, nafs al-lawwamah, and nafs al-muthmainnah. This research uses a descriptive qualitative approach, employing comparative-conceptual analysis and tematic (maudhu’i) exegesis of Quranic verses related to nafs. The result reveal a progressive correpondence between Hawkins levels of consciousness theory and the Quranic concept of nafs, especially regarding human spiritual evolution from egoistic impulses toward divine awareness. The integration of these two perspectives offers an important contribution to developing an Islamic-based spiritualpsychology paradigm that is both scientific and transdental.